13th International Hypoxia Symposium (2003)
Abstracts der auf dem 13. Internationalen Hypoxiesymposium in Banff (Kanada) gehaltenen Vorträge zu folgenden inhaltlichen Schwerpunkten: - Herzkreislaufprobleme und Training in der Höhe - neue Hypothesen zur Hypoxie - aktuelle Themen in der Hypoxieforschung - aktuelle Themen der Geburtsmedizin u.a. folgende Vorträge: LIVING HIGH-TRAINING LOW: EFFECT ON ERYTHROPOIESIS AND AEROBIC PERFORMANCE IN HIGHLY TRAINED CROSS-COUNTRY SKIERS. GENETIC MARKER FOR THE ERYTHROPOIETIC RESPONSE TO ALTITUDE. SLEEP CHARACTERISTICS IN ACUTE NORMOBARIC HYPOXIA IN RECREATIONAL ATHLETES. EFFECTS OF ACUTE EXPOSURE TO 1000 TO 4500 M ON VO2MAX IN ENDURANCE-TRAINED SUBJECTS. ALTITUDE STRATEGIES FOR MAXIMIZING CYCLE SPEED. THE PHYSIOLOGICAL AND PSYCHOLOGICAL IMPACT OF INTERMITTENT HYPOXIC TRAINING (IHT) IN THE PREPARATION OF THE THE GB BIATHLON TEAM FOR THE 2002 OLYMPIC GAMES. EFFECTS OF INTERMITTENT HYPOXIC TRAINING ON ACCLIMATIZATION IN ELITE CROSS-COUNTRY SKIERS.